Quantum turbulence and thermodynamics on a trapped Bose-Einstein condensate - Shiozaki, Rodrigo Figueiredo (2013)
In this thesis we have basically studied two aspects of BoseEinstein condensation (BEC) in trapped dilute gases: (i) superfluidity with the possible onset of quantum turbulence (QT), and (ii) nonuniformity, which suggests the definition of new variables in order to build a global thermodynamic description. Both analyses were performed in a 87Rb BEC magnetically trapped in a QuadrupoleIoffe configuration (QUIC) trap. Concerning the first item, vortices and QT were generated by applying an oscillatory excitation formed by a quadrupole magnetic field superimposed onto the QUIC trapping potential. Scanning both the excitation amplitude and its duration allowed us to observe different regimes, particularly one with regular, welldefined vortices and another, where the onset of QT is believed to have occurred. The transition between this two regimes were explained by considering the finitesize characteristic of trapped gases. Additionally, data analyses on three vortex configurations suggested the presence of both vortices and antivortices (opposite circulation sign), and the vortex nucleation mechanism was proposed to be related to a relative motion between the condensate and thermal components, namely a counterflow. As for the second item, the BEC transition in our experiment was characterized in terms of new global thermodynamic variables. A phase diagram was constructed and compared to the superfluid helium phase transition. Finally, we provide preliminary results on the calculation of a global heat capacity, and briefly discuss the advantages of this new approach over the local density approximation alternative, particularly on BEC clouds in the presence of vortices and QT.